PENGARUH PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) DIINTEGRASIKAN DENGAN STUDENT TEAM ACHIVEMENT DIVISION (STAD) TERHADAP KEMAMPUAN BERPIKIR TINGKAT TINGGI DAN KETERAMPILAN SOSIAL - Nurjannah, Umi; Prayitno, Baskoro Adi; Ariyanto, Joko (Pendidikan Biologi, 2012)
ABSTRACT ? This research purposed to know the influence of learning  PBI+STAD towards higher level of social and thinking skill of 10th  grade students in SMA Negeri Colomadu school year 2011/2012.  PBI+STAD  are combined learning models of syntax PBI on STAD. This research is a  quasi experimental  research using  Posttest Only Control Group Design. The independent variable was the model of PBI+STAD learning. The dependent variable is the higher order thinking and social skill of students. General population is all 10th  grade students from second semester in SMA Negeri Colomadu Karanganyar school year 2011/2012. The sampling technique used Cluster random Sampling. Samples in this research are class X-2 as an experiment class using a model of PBI+STAD and the class X-7 as a control class using models of learning that vary with lectures, discussions, and demonstrations. The technique of data collection of higher order thinking skill used technique test. The measurement of social skill used a questionnaire.  Prerequisite test analysis consisted of normality test and homogeneity test. Normality test was done with Kolmogorov Smirnov method. Normality test results indicated that the data were normally distributed. Homogeneity test applied Levene?s Test. The result showed that all groups are homogeneous. Data analysis technique for testing of hypothesis in this research is t-test with the aid of SPSS program version 16 significance level 5%. The result showed that higher order thinking are t0 > ttabel = 2.00 > 0.104 and social skill are t0 > ttabel = 2.00 > 1.51. The research concluded that  (1) PBI+STAD learning model does not affect the higher order thinking skills in 10th  grade students in  SMA  Negeri Colomadu Karanganyar,  (2) PBI+STAD  learning model does not affect the social skills in 10th grade students in SMA Negeri Colomadu Karanganyar. Keywords: PBI, STAD, PBI+STAD, Higher Order Thinking, Social Skill